2017
DOI: 10.1080/13691058.2017.1316424
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to use short-term oral pre-exposure prophylaxis (PrEP) by migrant miners and female partners of migrant miners in Mozambique

Abstract: Migrant miners from Mozambique who work in South Africa and their partners are at substantial risk for HIV infection. We conducted a cross-sectional study to assess the willingness of migrant miners and female partners of miners to take short-term pre-exposure prophylaxis (PrEP) for prevention of HIV acquisition. The study was conducted in Gaza Province, Mozambique, between September and October 2015. A total of 131 male miners and female partners of male miners completed a questionnaire. Subsequently, 48 in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Side effects, or fear of potential side effects, were common in both efficacy and implementation studies. Initial side effects among female partners of migrant mine workers in Mozambique dissipated over time but were tolerated because they took the side effects to mean that PrEP was working . Concerns about side effects during discussions of theoretical acceptability were common among women in one study, including partners in serodiscordant couples, adolescent girls and young women (AGYW), and sex workers .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Side effects, or fear of potential side effects, were common in both efficacy and implementation studies. Initial side effects among female partners of migrant mine workers in Mozambique dissipated over time but were tolerated because they took the side effects to mean that PrEP was working . Concerns about side effects during discussions of theoretical acceptability were common among women in one study, including partners in serodiscordant couples, adolescent girls and young women (AGYW), and sex workers .…”
Section: Resultsmentioning
confidence: 99%
“…However, male and female sex workers overall were supportive of the idea of PrEP providing "added protection" even in the context of aspirations to always use condoms [27]. Additionally, three other papers noted that risk behaviour did not change over time among participants actually using PrEP including migrant workers and female partners, MSM, FSW and serodiscordant couples [36,42,43]. It should also be noted that two systematic reviews also have shown no significant changes in behaviour among PrEP users [1,17].…”
Section: Realities and Compensationmentioning
confidence: 97%
See 1 more Smart Citation
“…Much qualitative research on antiretrovirals for prevention in Africa reports user perspectivesattitudes, knowledge, preferences, and influences on the use of PrEP and immediate ART [16][17][18][19][20][21][22][23][24][25][26]. Qualitative methods have also been used to shed light on reasons underlying suboptimal PrEP adherence in the VOICE and FEM-PrEP clinical trials [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The high acceptability and uptake are consistent with findings from our previous qualitative study in this population. 16 …”
Section: Discussionmentioning
confidence: 99%